Model Owens Kadakia-Learning Cluster Design untuk Meningkatkan Keterampilan Numerasi, Komunikasi, dan Berpikir Kritis Matematika Kelas I Sd XYZ Bekasi - Priska Yovita Tri Wahyuningrum Wulandari (Jurnal Syntax Admiration, 2024)
This study aims to analyze the difference between numeracy, critical thinking and communication skills in classes that apply OK-LCD with classes that apply the lecture method. The subjects of the study were grade I elementary school students in Bekasi totaling 28 people for the control class and 27 people for the experimental class. The study period was conducted for four weeks starting October 2 to October 20, 2023. This study used a weak experimental design method with a static-group pretest-posttest design model. Research data are obtained through written tests and rubrics that have been tested for validity and reliability. The results of the analysis and statistical tests showed the difference in control class pretest scores with control class post test, experimental class pretest scores with experimental class post test, and control class nGain with experimental class nGain on numeracy skills, critical thinking rubrics, and student communication rubrics. The data were expressed in the average nGain in the experimental class for numeracy, critical thinking and communication skills with consecutive scores of 0.56; 0,57; and 0.66. On average nGain in the control class for numeracy, critical thinking, and communication skills with consecutive scores of 0.40; 0,42; and 0.59. Therefore, it can be concluded that there is an increase in numeracy, critical thinking and communication skills in the control class and experimental class.